Perancangan Sistem Informasi Raport Online Berbasis Web - Nia Raficha (Universitas Labuhanbatu, 2021)
With the rapid advancement of technology, many educational institutions have not yet utilized the information system. The marking of grades of Kindergarten students Aisyiyah Bustanul Athfal still uses manual methods, allowing teachers to make mistakes when entering grades. Raport Online information system is an information system used for web-based kindergarten by using the PHP programming language and Codeigniter Framework. The design used in making functional requirements tables, use case diagrams, activity diagrams, sequence diagrams and interface design. The Raport Online information system is expected to improve teacher performance to enter grades.